Finding Love That Lasts: Breaking the Pattern of Dead End Relationships - Maas, Vera Sonja (Rowman & Littlefield Publishers, 2012)
Why do people find themselves repeatedly single when they are desperately searching for the perfect soul-mate with whom to share their future lives? In their determination to find the perfect partner, individuals’ perception is less than accurate when blinded by emotions, expectations, or wishful thinking. Consequently, having made decisions based on incomplete information, all too often, people find themselves once again at the breakup of what had seemed to be a promising relationship. The time has come for dispelling the notion that ‘love is blind’ and for exploring paths that have a more promising outlook for happy endings, paths that include the wisdom of knowing oneself and the willingness to face prospective partners with open eyes and an inquiring mind before considering any commitment. Finding Love that Lasts is not a book about saving or improving relationships; rather it is a book about the often unfortunate combinations of partners deciding to commit to each other for significant parts of their lives and the ways in which people can break the patterns that cause them to seek out similar partners and relationships that are often doomed to fail. Here, Maass explains why people repeat the patterns that cause them to end up in failed relationships. Case histories from patients, volunteers from the general community, and participants in personal growth groups, help offer insight into the negative patterns people commonly repeat in their search for lasting love and companionship. Readers will come away from this book with a better understanding of those patterns, how to recognize and break them, and how to move forward to healthier and more rewarding relationships.